Electrochemical Behaviour of 3-Ethyl-1-phenyl-3-hydroxytriazen - Gupta, Manu; Karnawat, R.; Sharma, I.K.; Verma, P.S. (Asian Journal of Chemistry, 2010)
3-Ethyl-1-phenyl-3-hydroxytriazene (EPHT) was synthesized, purified and characterized by elemental analysis and spectral studies. Electrochemical reduction of EPHT has been studied at various scan rates at glassy carbon electrode (GCE) and platinum electrode by cyclic voltammetry. The kinetic parameters have been evaluated. 3-Ethyl-1-phenyl-3-hydroxytriazene reduction appears to involve irreversible electron transfer in the potential range 800-1500 mV vs. Ag, AgCl. Controlled current electrolysis of EPHT was also carried out using stainless steel (SS-316) electrodes. The proposed mechanism of the reduction is discussed in acidic, neutral and basic media.